Email and commercial correspondence : a guide to professional english - Wallwork, Adrian (Guides to Professional English, 2014)
If you write emails and letters as part of your work, then this book is for you. By applying the suggested guidelines, you will stand a much greater chance of getting the desired reply to your emails in the shortest time possible. Some of the key guidelines covered include: Write meaningful subject lines - otherwise recipients may not even open your mail. Always put the most important point in the first line - otherwise the reader may not read it. Be concise and only mention what is truly relevant. Write the minimum amount possible - you will also make fewer mistakes! Be a little too formal than too informal - you don't want to offend anyone. If you have two long important things to say, say them in separate emails. Give clear instructions and reasonable deadlines. If you need people to cooperate with you, it is essential to highlight the benefits for them of cooperating with you. Empathize with your recipient's busy workload. Never translate typical phrases literally - learn equivalent phrases. The book concludes with a chapter of useful phrases. There is also a brief introduction for trainers on how to teach Business / Commercial English. Adrian Wallwork is the author of over 30 books aimed at helping non-native English speakers to communicate more effectively in English. He has published 13 books with Springer Science+Business Media. Other books in this Professional English series: CVs, Resumes, and LinkedIn User Guides, Manuals, and Technical Writing Meetings, Negotiations, and Socializing Presentations, Demos, and Training Sessions Telephone and Helpdesk Skills